Izhodišča etnološkega in antropološkega raziskovanja izgorelosti - Habinc, Mateja (Etnolog. Nova vrsta (Ljubljana), 2023)
This article examines workplace burnout by looking at the media and various peer-reviewed publications, in particular the definitions of the phenomenon and the topics that have received the most research attention. It shows that in Slovenia, as in other countries, burnout is medicalised and professional efforts to adopt systemic measures for the prevention of or dealing with burnout tend to follow the situation in developed Northern European welfare states. It highlights aspects of burnout that call for ethnological or (cultural) anthropological approaches and presents the starting points for such efforts.
Keywords: antropologija; bolezen; etnologija; izgorelost; Slovenci; zdravje